Shock Loading-Unloading Mechanism in Rockburst Shear Fractures in Quartzite Causing Genesis of Polyhedral Sub-Particles in the Fault Gouge - Tarasov, BG; Ortlepp, WD (Deep Mining 2007: Proceedings of the Fourth International Seminar on Deep and High Stress Mining, 2007)
The presence of polyhedral sub-particles in dynamically-formed shear zones in quartzite is a specific manifestation of a very complicated and still enigmatic mechanism of shear fracture development. The existence of these sub-particles allows disclosure of one important feature of this mechanism. Comprehensive analysis of the geometrical shape of the sub-particles gave reason to conclude that the most plausible explanation of their formation is shock unloading taking place in the fracture zone. At the same time the fact that a relatively minute and very strong quartz grain can be disrupted into elemental sub- particles of approximately 25 micrometres in size must indicate the presence of enormous amount of energy within the grain before the shock unloading. This energy can be provided, in particular, by shock loading preceding the shock unloading. The paper discusses a new shear rupture mechanism which can provide the combination of extreme dynamic compressive loading followed by shock unloading within some special zones of the fault. According to this mechanism a general fault develops as a cascade of segments triggered in series one after another. Interaction and linkage of the segments propagating toward each other at a relative speed comparable with shear wave speed can cause shock-like loading-unloading impulses necessary for the particle formation due to specific structure of linkage zones.